Construção participativa de uma matriz de indicadores para avaliação de programas de educação ambiental aplicados na gestão de recursos hídricos no semiárido - Santos, Jackeline Lisboa Araújo (2013)
The articulation of semiarid (ASA) through P1MC (Training and Social Mobilization Program for living with semiarid: One million rural cisterns), enables families who live in rural areas have access to the cistern plates, a technology that aims to collect rainwater and store it for human consumption. Along with this action, the program has the development of the training course in Water Resources Management (GRH) as a form of social mobilization. The aim of this study was to construct, with the participation of subjects involved in the construction of cistern program, a matrix of indicators for evaluating environmental education programs applied in water resources management. This research has a qualitative approach and its object of study was the P1MC, performed by unit MOC (Movement of Community Organization) located in Serrinha municipality, Bahia state. The research subjects were twenty representatives of families benefiting with the cistern, two multipliers technicians and two GRH course instructors. Data collection had two stages: the first stage consisted on the primary indicators matrix construction, based on interviewssemistructured, documentary research and observation GRH courses. The second stage consisted on matrix finalization and validation, accomplished through focus group, composed of participating subjects: two members of the Water Resources Commission of the municipality, two multipliers technicians, an instructor, a community health worker and a community representative. The constructed matrix of indicators is based on seven dimensions (social, political, educational, cultural, environmental and public health, economic, spatial organization of dialogue) and sixteen indicators with guiding questions, descriptors and means of verification. It is expected that the use of indicators matrix for evaluating environmental education programs can contribute as an instrument that introduces functionality and can be easily applied in the evaluation and monitoring of Environmental Education courses in the construction of cisterns programs.